2021
DOI: 10.11113/lspi.v8.17182
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Literature among Pre-Service Teachers: Challenges and Solutions

Abstract: Teacher trainees should be prepared to teach and exposed to the approaches, models, and techniques of literature teaching. Being ready can also boost their confidence to teach literature so that the lessons can be delivered smoothly.  These teachers are so new to teaching that they might face difficulties when teaching English, specifically literature. There are teaching techniques, strategies and approaches that those pre-service teachers can investigate to understand better how to apply in their teaching. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Noraishah et al (2015) reported that students are lacking in focus and co-operation in class during literature lesson due to teachers' weakness in giving good explanations and elaboration on the literature text. Several articles also mentioned that teachers still succumb to the old traditional ways of dull and less creative literature teaching and refuse to try new interesting techniques of teaching (Faiza & Azlina, 2020;Harwati & Mohamad Asyraf, 2019;Yahya, 2017;Ain Suraya & Norhanim, 2021).…”
Section: ) Inappropriate Teaching Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Noraishah et al (2015) reported that students are lacking in focus and co-operation in class during literature lesson due to teachers' weakness in giving good explanations and elaboration on the literature text. Several articles also mentioned that teachers still succumb to the old traditional ways of dull and less creative literature teaching and refuse to try new interesting techniques of teaching (Faiza & Azlina, 2020;Harwati & Mohamad Asyraf, 2019;Yahya, 2017;Ain Suraya & Norhanim, 2021).…”
Section: ) Inappropriate Teaching Methodsmentioning
confidence: 99%
“…Next, four articles stated that students who view literature in a negative way are not interested in the literature lesson itself (Ugwu, 2022;Farhanah & Hadina, 2022;Ain Suraya & Norhanim, 2021;Gatdula et al, 2022). Ugwu (2022) specifically mentioned that students undervalue the need to learn Literature in English as a school subject, which can negatively influence their attitude towards it.…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations